Is it Application of Extended Writing Truly Push Writing Student Ability? - Ismail Ismail (Edumaspul: Jurnal Pendidikan, 2017)
The extended writing allowed the incorporation of the process into the assessment of writing skills and encouraged increased students autonomy. The research was conducted through a classroom action research (CAR) that comprising 18 students. The results of the student's writing text in the cycle 1 and cycle 2 had increased in different scores. The means scores in data source where 61.67 become 63.61 in cycle 1, and after revision, in the cycle 2, the mean score in cycle 2 was 74.72 by application of extended writing project assessment. The successful minimal criterion (KKM) was 70. It can be seen that the application of Extended Writing Project Assessment was increased significantly. The most obvious consequence of this is that the ideas presented by the students are better, and the time needed to complete an essay is much more efficient.